Early warning processing results and algorithm improvement for doublet earthquakes in different locations in Xinjiang - Weiheng Yu; Shuilong Li; Shiwen Zhou (地震科学进展)
The calculation of early warning for earthquakes remains an unresolved challenge worldwide. Doublet earthquakes are complex, and different events can vary significantly. In April 2023, doublet earthquakes occurred at various locations in Xinyuan County, Xinjiang Province. The Fujian earthquake early warning system responded quickly and released three early warning reports. The first report was issued 27.4 s after the first station was triggered, using data from six stations. Compared to the official earthquake catalog, the epicenter deviation was 131.54 km and the magnitude deviation was 3.4. By analyzing the time sequence and spatial distribution of triggered stations, we found that different earthquakes may have been incorrectly associated with the same event. Errors in determining the first triggered station led to significant deviations in the calculated location and magnitude. The processing algorithm for doublet earthquakes within the early warning system must be improved. The range of earthquake influence can be estimated using peak acceleration attenuation, and the reliability of the first station can be evaluated by analyzing the triggering ratio of surrounding stations. These measures can help improve the off-site doublet earthquake processing algorithm in the Fujian early warning system.